2016
DOI: 10.1155/2016/4834851
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation Criteria for Comparative Intradermal Tuberculin Test for Diagnosis of Bovine Tuberculosis in Cattle in Maroua Area of Cameroon

Abstract: Intradermal tuberculin test (TST) is the choice method for diagnosis of bovine tuberculosis (Tb) in live animals. This work was done to assess the performance of single intradermal comparative cervical tuberculin (SICCT) test in randomly selected cattle in Maroua, Cameroon, against detection of Tb lesions and detection of Tb lesions plus acid fast bacilli in lesions. While 22.28% of slaughtered cattle presented Tb lesions at meat inspection, detection rates of anti-bovine-Tb antibody, Tb lesions, and Tb lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The OIE recommended cut-off for SICCT interpretation is 4 mm, however, many studies showed that a severe cut-off of 2mm increased the sensitivity of the test [ 67 , 68 ], without affecting the specificity compared to the recommended cut-off [ 69 ]. Consequently, we decided to consider both 2mm and 4mm cut-offs in the model, and to compare the respective results.…”
Section: Methodsmentioning
confidence: 99%
“…The OIE recommended cut-off for SICCT interpretation is 4 mm, however, many studies showed that a severe cut-off of 2mm increased the sensitivity of the test [ 67 , 68 ], without affecting the specificity compared to the recommended cut-off [ 69 ]. Consequently, we decided to consider both 2mm and 4mm cut-offs in the model, and to compare the respective results.…”
Section: Methodsmentioning
confidence: 99%
“…The intradermal tuberculin test is an inexpensive test used for TB diagnosis in cattle for both latent and active infections [ 5 ]. However, the method has limited sensitivity and specificity and is influenced by many factors related to immunological response [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Diagnosis of TB requires measuring either a humoral or cellular immune response. The tuberculin test is the test of choice globally and the most common test for bovine TB and international trade [ 5 ]. However, the tuberculin test is limited by variable specificity and sensitivity due to common skin reactive antigens that cause reactions in animals sensitized to non-tuberculous mycobacteria [ 6 ].…”
Section: Introductionmentioning
confidence: 99%